The Successful Use of Infliximab in a Relapsing Case of Susac’s Syndrome - Suran L. Fernando; Therese Boyle; Annika Smith; John D.E. Parratt (Case Reports in Neurological Medicine)
Susac’s syndrome is a rare and debilitating disease characterized by the triad of encephalopathy, branch retinal artery occlusions, and sensorineural hearing loss. All manifestations may not be clinically apparent at presentation resulting in delayed diagnosis. Early recognition of the syndrome may prevent disease sequelae such as permanent cognitive, visual, and hearing loss. We present such a case of Susac’s syndrome that was also refractory to conventionally prescribed combination of immunosuppressive treatments including high-dose potent corticosteroids, intravenous cyclophosphamide, methotrexate, plasma exchange, rituximab, and mycophenolate. His disease was stabilized with infliximab in combination with a tapering course of low-dose prednisone. After 2 years of remission with TNF treatment, consideration is being given to ceasing therapy. He has the sequelae of bilateral sensorineural hearing loss but no visual impairment or cognitive deficits on follow-up with neuropsychometric testing. This is the first case report to our knowledge of the successful use of infliximab for a patient with Susac’s syndrome that was necessary following treatment with cyclophosphamide and then rituximab.